2021
DOI: 10.3389/fmars.2021.793118
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Role of Glutamine synthetase Gene on Ammonia Nitrogen Detoxification Metabolism of the Razor Clam Sinonovacula constricta

Abstract: Ammonia nitrogen is a common toxic substance in the aquatic system, which seriously threatens the survival and growth of clams. However, less is known about the ammonia metabolism and detoxification strategy in razor clam. In this study, the polymorphism of the Glutamine synthetase gene from Sinonovacula constricta (Sc-GS) was found to be related to ammonia tolerance. By comparing the coding sequence (CDS) region of Sc-GS from two geographical populations, a total of 14 and 12 single nucleotide polymorphisms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In addition, an unnegligible pathway of detoxifying ammonia into urea, which had been commonly found in the liver of ureogenic animals, maintained low concentration of ammonia. It occurs principally through ornithine-urea cycle involving catalysis of crucial enzymes, including arginase (ARG), argininosuccinate synthetase (ASS), and GS (Mommsen and Walsh, 1989;You et al, 2018;Sun et al, 2021). Although the study on molecular mechanism underlying regulation expose to ammonia in molluscs is still at its infancy, preliminary studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an unnegligible pathway of detoxifying ammonia into urea, which had been commonly found in the liver of ureogenic animals, maintained low concentration of ammonia. It occurs principally through ornithine-urea cycle involving catalysis of crucial enzymes, including arginase (ARG), argininosuccinate synthetase (ASS), and GS (Mommsen and Walsh, 1989;You et al, 2018;Sun et al, 2021). Although the study on molecular mechanism underlying regulation expose to ammonia in molluscs is still at its infancy, preliminary studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Of the top 10 sensitive genera, eight genera belong to molluscs (USEPA, 2013). However, the clam-fish/shrimps polyculture makes razor clam to face to high concentration of ambient ammonia (Sun et al, 2021). Therefore, S. constricta is a suitable model species to explore the molecular mechanism of higher tolerance to ammonia in molluscs.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, as benthic animals are often faced with higher ammonia concentrations compared with pelagic animals, they have evolved several mechanisms to adapt to high ambient ammonia [19]. In fact, excellent ammonia tolerance has been found in many marine bivalves, especially S. constricta, which lives under 30-40 cm of mud in ponds with an extreme high ammonia concentration [22,29]. A majority of aquatic invertebrates are ammonotelic and excrete ammonia primarily in the form of NH 3 or NH 4 + , rather than relying on ammonia metabolism [19,30].…”
Section: Discussionmentioning
confidence: 99%